Comparative In Vitro Activities of Caspofungin and Micafungin, Determined Using the Method of the European Committee on Antimicrobial Susceptibility Testing, against Yeast Isolates Obtained in France in 2005-2006 - Dannaoui, E.; Lortholary, O.; Raoux, D.; Bougnoux, M. E.; Galeazzi, G.; Lawrence, C.; Moissenet, D.; Poilane, I.; Hoinard, D.; Dromer, F. (Antimicrobial Agents and Chemotherapy, 2008)
Classifications Services AAC Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue AAC About AAC Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy AAC RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 0066-4804 Online ISSN: 1098-6596 Copyright © 2014 by the American Society for Microbiology. For an alternate route to AAC .asm.org, visit: AAC